Magma Genesis in Kabanjahe Region Continental Margin Arc of Sumatra - HaraHap, Bhakti H. (Geological Agency, 2011)
DOI:Â 10.17014/ijog.v6i2.120Volcanic rocks in Kabanjahe region, Karo Regency, North Sumatra Province, are products of old Toba Caldera, Sibayak Volcano, and Sipiso-piso Volcano. Rhyolitic tuff is the main lithology distributed over a large area in this region. Others are basaltic, basaltic andesitic, andesitic, dacitic, and rhyolitic lavas. Data show that the rock was originated from magma of a continental origin formed at a subduction zone environment. Petrogenetic modelling suggests that the range in composition was mainly controlled by a fractional crystallization of plagioclase, clinopyroxene, hornblende, and biotite. Harkerâs variation diagram of major and trace elements show a continuous range that indicates they are cognate. The lava in this area belongs to a high-K, calc-alkaline series, with particular high Nb concentrations. The composition of these high-Nb lavas is more similar to those of intra plate basalts rather than those of calc-alkaline or arc-tholeiitic basalt. The high anomaly of Nb whichÂ is accompanied by high Th, Rb, and normative corundum suggests that the source may also be enriched in incompatible elements, a characteristic feature of alkali magmatism. The similarity of the trace element of volcanic rocks to the within-plate basalts indicates that the convecting mantle wedge above subducted slabs contains variable proportions of MORB-source and OIB-source components; fluids added were derived from the subducted slab. Hence, it is interpreted that the high Nb concentration of volcanic rocks from Kabanjahe region were generated from subduction modified OIB source components. Alternatively, a deep seated faulting conduit magma from the lower mantle resulted in the alkaline enrichment of the volcanics. This article performs a petrological aspect, especially based on geochemical analysis including major elements, trace elements, and rare earth elements. The results are plotted into a general and specific classification used in petrology.